Measures of Dosage for Spinal-Cord Electrical Stimulation: Review and Proposal - Peter S. Single; Jonathan B. Scott; Dave Mugan (IEEE, 2023)
This manuscript proposes an electrical definition of therapeutic dose for spinal-cord systems used for the treatment of chronic pain, analogous to the pharmacological definition. Dose-response relationships are fundamental to pharmacology, radio-therapy, and other treatments, but have never been properly established for neuromodulation. This manuscript offers a robust measure of dose, pre-requisite to establishing a reliable and repeatable dose-response relationship. The new definition, enabled by the system transresistance obtained from measurement of evoked action potentials, recognizes the mechanism of action of spinal cord stimulation (SCS), and should improve acceptance of the therapy as compared to pharmacological treatments which are currently used more frequently for the treatment of chronic pain. The new definition suggests methods for personalization and standardization of the dose in SCS, and is potentially generalizable to all neuromodulation therapies in which nervous tissue is excited including sacral nerve stimulation (SNS), vagal nerve stimulation (VNS) and deep-brain stimulation (DBS). Formulas are provided, and applied using patient data. Powerful conclusions are drawn from application of the new measure.